Effects of Metarhizium anisopliae and Red Ginger Extract (Zingiber officinale var.rubrum) on Feeding Behaviour and Mortality of Spodoptera litura Larvae - Johana Anike Mendes; Rangga Kusumah; Jefri Sembiring; Mariana Resubun; Ade Kurniawan (Journal of Biotechnology and Natural Science, 2026)
The management of Spodoptera litura, a major pest of vegetable crops, is still predominantly reliant on synthetic pesticides, whose excessive use raises concerns regarding environmental safety and human health. This study investigated the effects of the entomopathogenic fungus Metarhizium anisopliae and red ginger extract (Zingiber officinale var rubrum), applied individually on feeding behaviour and larval mortality of S. litura. Laboratory bioassays were conducted using the leaf-dipped method to evaluate larval mortality. Feeding inhibition activity of red ginger extract was assessed using choice and no-choice test. Red ginger extract caused 48% larval mortality at a concentration of 2 ml/50 ml of water, while M. anisopliae resulted in 28% larval mortality at 20 g/50 ml of water. Feeding inhibition under the choice test was categorized as very weak (10.20%) at 2 ml/50 ml of water, similarly M. anisopliae did not exhibit feeding inhibition under either test method